Systematic Literature Review: Kemampuan Komunikasi Matematis Siswa Ditinjau dari Gaya Berpikir - Sutopo, Lintang Agmahira; Waluya, Stevanus Budi (Indonesian Journal Publisher, 2024)
Mathematical communication skills encompass the oral and written abilities of students regarding the mathematical concepts they possess. The aim of basic mathematics education involves cognitive and social activities so that in communicative situations, students can enhance their learning interactions with others to obtain mathematical ideas. They should be capable of conveying their mathematical thoughts to others, developing mathematical concepts and strategies, and reflecting on their understanding of mathematics. Thinking styles are cognitive patterns that differentiate how students receive and process information and then use that information to solve problems, particularly in mathematical problem-solving. The objectives of this research are (1) to identify the types of research used in mathematical communication skills concerning thinking styles published in the last 5 years, (2) to identify research trends on mathematical communication skills and thinking styles in the last 5 years, and (3) to reveal the influence of students' thinking styles on mathematical communication skills, including the interpretation of mathematical problems, the selection of solution strategies, and mathematical problems solving abilities. The research method employed in this study is the Systematic Literature Review (SLR). Data collection involves reviewing articles related to students' mathematical communication skills concerning thinking styles published between 2018 and 2023. The findings indicate that (1) qualitative research is the most commonly used type of research, (2) research is predominantly conducted at the junior high school level, and (3) thinking styles significantly influence students' mathematical communication skills.